2021
DOI: 10.1108/mbe-08-2019-0084
|View full text |Cite
|
Sign up to set email alerts
|

Performance habitus: performance management and measurement in UK higher education

Abstract: Purpose What academic and managerial elements are particularly influential regarding performance? This study aims to address these questions as part of a broader longitudinal study. The current paper focusses on the results relating to performance management and measurement, and how the sectorial developments impacted on individuals and institutions. Design/methodology/approach An interpretive research methodology was used, which illustrates the institutional performance management and measurement system. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Studies have indicated NPM causing excessive workload for academics. The assertive nature of HR functions continues to control line managers’ ‘highly variable’ behaviour (Guarini et al 2020 ; Hutaibat et al 2021a , b ), with ‘harder measures’ (Clarke and Knights 2015 ). The major issue in implementation of Performance Management systems in academia is its data-driven nature.…”
Section: Problems In Performance Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have indicated NPM causing excessive workload for academics. The assertive nature of HR functions continues to control line managers’ ‘highly variable’ behaviour (Guarini et al 2020 ; Hutaibat et al 2021a , b ), with ‘harder measures’ (Clarke and Knights 2015 ). The major issue in implementation of Performance Management systems in academia is its data-driven nature.…”
Section: Problems In Performance Managementmentioning
confidence: 99%
“…The British higher education sector is currently going through an unprecedented transformation (Hutaibat et al 2021a , b ). Shrinking public funding, together with the new fees regime introduced by an overwhelming majority of British universities is creating significant financial pressure on the British higher education sector (Hutaibat et al 2021a , b ). As students pay more, they expect more in terms of academic quality and employability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, attention was focused on the UK education sector, as this research was aimed at evaluating one of the UK universities. Based on the literature, it is evident that few researchers have conducted studies exploring the application of performance appraisal methods and approaches in the UK higher education institutions in particular [44].…”
Section: Performance Appraisal In Higher Educational Institutionsmentioning
confidence: 99%
“…Consequently, several researchers have recommended using a contingency approach (i.e., there is no best way to manage employees and it should be tailored according to a particular organisation) for PA of the higher education sector rather than the formal best-practice method [47]. The relevance of such an approach is even more relevant with tuition fees of students being doubled and students taking the role of customers; academics are faced with higher expectations and the idea of job uncertainty and performance expectations introduced to their work-life [44].…”
Section: Performance Appraisal In Higher Educational Institutionsmentioning
confidence: 99%